NEED ANALYSIS FOR IDENTIFYING ESP MATERIALS FOR MEDICAL RECORD STUDENTS IN APIKES CITRA MEDIKA SURAKARTA - Setiawati, Beta (Universitas Muhammadiyah Surakarta, 2016)
Identifying teaching material is the process of Â selecting, adapting and evaluatingÂ of teaching based on specific necessities of the students. Need Analysisis really needed to identify teaching materials for Â English for Specific Purpose.Â The researchobjective is toidentify the ESP materials for teaching 3rd semestermedical record students at Academy of Medical Record and Health informationÂ Citra Medika (APIKES CITRA MEDIKA) Surakarta. The work used qualitativeand quantitative methods. The outcomesof this study showed the real necessitiesÂ of students in learning English to prepare their future at the field of medical recordÂ and health information. Findings of the need analysis demonstrate that allÂ four of the language skills were necessary for their academic studies and theirÂ target career. There are certain topics related to English for medical record suchÂ as medical record staffâ duties, ethical and legal issues in medical record, HospitalÂ statistics, Medical record filling system, Health information system, and soÂ on. Accordingly, this study proposes new ESP materials based on the stakeholdersâÂ needs.It is suggested that textbook or handout of English for Medical RecordÂ will be made based on the Need Analysis by ESP designers and ESP lecturersÂ involve actively recognizing the progressive needs of medical record students.